2006
DOI: 10.1590/s0100-879x2006000500002
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma-associated herpesvirus infection and Kaposi's sarcoma in Brazil

Abstract: Kaposi's sarcoma (KS) became a critical health issue with the emergence of acquired immunodeficiency syndrome (AIDS) in the 1980s. Four clinical-epidemiological forms of KS have been described: classical KS, endemic KS, iatrogenic KS, and AIDS-associated KS. In 1994, Kaposi's sarcoma-associated herpesvirus (KSHV) or human herpesvirus type 8 was identified by Chang and colleagues, and has been detected worldwide at frequencies ranging from 80 to 100%. The aim of the present study was to evaluate the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…An Iranian study reported the presence of HHV-8 DNA in 83.3% (30/36) of the KS tissues [ 1 ]. Several other studies have also reported high detection rates of HHV-8 DNA in KS tissue biopsies [ 28 30 ]. Our findings along with those from other studies emphasize the pathogenic role of HHV-8 in the development of KS [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 94%
“…An Iranian study reported the presence of HHV-8 DNA in 83.3% (30/36) of the KS tissues [ 1 ]. Several other studies have also reported high detection rates of HHV-8 DNA in KS tissue biopsies [ 28 30 ]. Our findings along with those from other studies emphasize the pathogenic role of HHV-8 in the development of KS [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies, since Chang et al. (25) , initial description, have reported the presence of HHV‐8 DNA in KS using PCR and immunohistochemical methods (15, 26–28). Accordingly, in the present study, all OKS cases were positive for HHV‐8, and as expected, it was negative in OPG (19).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies and case reports of KS and serologic studies of HHV‐8 in patients with AIDS in Brazil. There are no published data on the effect of ART on AIDS‐related KS in Brazil.…”
Section: Introductionmentioning
confidence: 99%